Effect of nitrazepam and flurazepam on the ventilatory response to carbon dioxide. Issue 5 (October 1976) - Geddes, D M; Rudolf, M; Saunders, K B
Abstract : Ventilatory response to CO2 was measured before and after two different benzodiazepine hypnotics in both chronic bronchitics and patients without chest disease. Flurazepam, but not nitrazepam, produced a significant decrease in CO2 sensitivity, although there was no significant change in FEV1 or mixed venous PCO2. This is the first unequivocal evidence of central depression of respiration by a benzodiazepine and may be the mechanism by which benzodiazepines cause deterioration in patients with respiratory failure.